Issues in Border Security of Nepal - Upreti, Yukesh (Journal of APF Command and Staff College, 2021)
Cross border is a major threat to the internal and external security of Nepal. To maintain peace and security and neutralize illicit trade, smuggling, and cross-border crimes, the Government of Nepal has deployed Security forces at the border. The Indo-Nepal border comparatively is challenging due to its open border status. This paper analyses the field issues faced by security personnel at border areas of Nepal. The study uses both primary and secondary data for analysis and interpretation. The findings show geographical problems, socio-economic similarities, operational problems, border laws, values, and ethics. These issues are faced by security forces daily. The study outcome suggests a need for a collaborative approach of stakeholders on strengthening border security.